TRANSNATIONAL ORGANIZED CRIME, TERRORIST FINANCING AND BOKO HARAM INSURGENCY IN NIGERIA - Adisa, Waziri (Journal of Terrorism Studies, 2021)
Terror attacks on the African continent have continued to impose significant costs on the people, particularly in the West African sub-region where Boko Haram and the Islamic State in the West African Province have remained active for the last decade. While the security threat that the Boko Haram insurgency poses to the West African sub-region has been well established in the literature, there is a dearth of studies on the role of transnational organized crime and terrorist financing in the wake of the sects’ activities in the sub-region. This article therefore argues that Boko Haram and ISIS in Nigeria have managed to sustain their campaigns based on financing from multiple sources within the complex transnational and transactional criminal networks in Nigeria and in most of the West African sub-region. In order to overcome this challenge, the article argues, there is need for effective counterinsurgency plans in Nigeria to go beyond military warfare and move to issues of inclusive governance that can drastically reduce criminality in the larger society.